Data-driven interpretation and optimization of crimson red dye adsorption using spirulina-derived hydrochar–CuO nanocomposites - B. Subha; S. Murugeshwari; B. Senthil Rathi; J. Divya; E. Krithya (Biomass and Bioenergy, 2026)

A Comprehensive Study on the Chemical, Biological, and Environmental Factors Shaping the Medicinal Value of Euphorbia hirta - J. B. Reshmi; P. S. Abitha; P. C. Divya; S. Grace Victoria; V. N. Meena Devi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2026)

Plant-Mediated CuO Nanoparticles for Reactive Orange Dye Adsorption: Experimental study and Machine Learning-Assisted Optimization - S. Murugeshwari; Madhan Gunasekaran; B. Senthil Rathi; R. M. Saravana Kumar; J. Divya (Water, Air, & Soil Pollution, 2026)

Polar Winter Processes: An Under-Represented Research Focus within the Coupled Earth System - Xin Yang; Xiangdong Zhang; Ankit Agarwal; Rajendran Shobha Ajin; Thomas J. Bracegirdle; Peter Convey; Rainette Engbers; Markus M. Frey; Eugenia M. Garbarini; Irina Gorodetskaya; Xianda Gong; Sergi González-Herrero; et al. (Advances in Atmospheric Sciences, 2026)
Observing winter processes during the extended cold season is crucial not only for understanding polar and global coupled Earth system but also for enhancing capability of year-round prediction, especially in the context of Arctic amplification and the drastic decrease in sea ice extent and thickness at both poles. However, harsh environmental conditions and logistical challenges have left polar winter Earth system processes substantially under-observed compared with those during summer. This disparity creates major obstacles for studying these processes and their roles in shaping the state and variability of the Earth systems, as well as for accurately simulating them in Earth System Models (ESMs). Consequently, these limitations introduce considerable uncertainties in ESMs regarding the understanding, prediction, and projection of Earth system variability and changes. This study discusses key polar winter processes and evaluates critical knowledge gaps. It identifies three urgent research priorities for the near future: (i) sources, properties, and transport of polar winter aerosols and their interactions with clouds; (ii) polar storms and their interactions with the underlying sea ice and ocean; and (iii) persistent discrepancies in understanding and predicting large-scale teleconnections between polar regions and lower latitudes. To address these priorities, this perspective recommends strengthening coordinated, winter-focused, international and multidisciplinary observational efforts, for example, through initiatives such as the Fifth International Polar Year and the ongoing international Antarctica InSync programme. These initiatives would lay groundwork for designing future sustainable winter process observations.

Intraspecific Variation of Edwardsiella anguillarum From Non‐Anguillid Fish From Varied Geographic Origins - Abigail R. Armwood; Divya Rose; Geoffrey C. Waldbieser; Ethan Woodyard; Bradley M. Richardson; Esteban Soto; Cynthia B. Stine; Cynthia C. Ware; Paola Barato; Alvin C. Camus; Matt J. Griffin (Journal of Fish Diseases, 2026)
Edwardsiella anguillarum is a gram‐negative bacterium, synonymous with previously described atypical, fish‐pathogenic Edwardsiella tarda . Originally described from eels in 2015, E. anguillarum is an important global fish pathogen, particularly in tilapia. This study describes intraspecific phenotypic and genotypic variability among 17 E. anguillarum isolates from non‐anguillid fish hosts and varied geographic origins. Isolates demonstrated similar biochemical characteristics, with slight variation in motility and hydrogen sulfide production. Genomic relatedness among isolates was analysed with repetitive extragenic palindromic sequence‐based PCR (rep‐PCR) and multilocus sequence analysis (MLSA). Rep‐PCR with the ERIC II primer set revealed two distinct genetic clusters, while amplification strategies utilising the GTG 5 , BOX or ERIC I&II primer sets yielded more uniform profiles. While rep‐PCR deemed the isolates largely clonal, MLSA schemes using reference genes from published Edwardsiella MLSA studies revealed E. anguillarum isolates formed five discrete phylogroups. A unique, ~91.5 kB plasmid was identified in Costa Rican and Colombian isolates, associated with conjugative and transposable elements, plasmid mobilisation, and adhesion; however, no plasmid mediated antibiotic resistance genes were identified. This study provides insight into genetic diversity among E. anguillarum isolates from different hosts and geographic regions, identifying an optimal MLSA scheme from previous reports applicable to E. anguillarum isolates.

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Microcystis aeruginosa detected in freshwater lakes in Meghalaya, India show strong hepatotoxicity - Waniabha J. Lyngdoh; Langpoklakpam James Singh; Ankita Dey; Divya Newar; Jopthiaw Nongdhar; Surya Bhan; Arvind Kumar Singh (Archives of Microbiology, 2026)

Frequency of γ-H2AX foci, micronucleus formation, and radiation dose to the blood lymphocytes in pediatric and adult participants underwent computed tomography imaging - Divya K. Mohan; Nandhini K.; Aishwarya S.; Senthil Kumar M.; Swetha K.; Akshaya J.; Sudha Pattan; Venkata Sai P.M.; Venkateswarlu Raavi; Venkatachalam Perumal (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2025)

The effect of α-tocopherol (vitamin E) on the phase behaviour of fully-hydrated dioleoyl phosphatidylcholine membranes - Chi Long Chan; Divya Malia; Miguel Paez-Perez; Laurent Sagalowicz; Olivier Schafer; Robert V. Law; Nicholas J. Brooks; John M. Seddon (Chemistry and Physics of Lipids, 2025)

Optimized biodiesel production from Java olive seeds using a novel magnetic nanobiocatalyst and advanced optimization techniques - L.R. Monisha Miriam; Ajith J. Kings; Jain B. Marshel; R. Edwin Raj; S. Indran; D. Divya (Biomass and Bioenergy, 2025)

Separating Historical Catches Among Pygmy Blue Whale Populations Using Recent Song Detections - Trevor A. Branch; Cole C. Monnahan; Emmanuelle C. Leroy; Fannie W. Shabangu; Ana Širović; Salvatore Cerchio; Suaad Al Harthi; Cherry Allison; Naysa Balcázar Cabrera; Dawn R. Barlow; Susannah V. Calderan; Michael C. Double; et al. (Marine Mammal Science, 2025)
In the Southern Hemisphere and northern Indian Ocean, there are at least five populations of pygmy blue whales, Balaenoptera musculus brevicauda , residing in the Northwest Indian Ocean (NWIO, Oman), central Indian Ocean (CIO, Sri Lanka), Southwest Indian Ocean (SWIO, Madagascar to Subantarctic), Southeast Indian Ocean (SEIO, Australia to Indonesia), and Southwest Pacific Ocean (SWPO, New Zealand). Each population produces a distinctive repeated song, but none have population assessments or reliable measures of historical whaling pressure. Here we created pygmy blue whale catch time series by removing Antarctic blue whale catches using length data and then fitting generalized additive models (based on latitude, longitude, and month) to contemporary song data (largely from 1995 to 2023) to allocate historical catches to the five populations. Most pygmy blue whale catches (97% of 12,207) were taken by Japanese and Soviet operations during 1959/1960 to 1971/1972, with the highest totals taken from the SWIO (6514), SEIO (2593), and CIO (2023), and lower catches from the NWIO (549) and SWPO (528). The resulting predicted annual catch assignments provide the first indication of the magnitude of whaling pressure on each population and are a key step toward assessing the status of these five pygmy blue whale populations.

Performance evaluation of existing and advanced processes for remediation of microplastics: A comprehensive review - Divya P. Barai; Swati L. Gajbhiye; Yogeshwary M. Bhongade; Hemant S. Kanhere; Dadasaheb M. Kokare; Nishikant A. Raut; Bharat A. Bhanvase; Sanjay J. Dhoble (Journal of Environmental Chemical Engineering, 2025)

Optimization of Crop Yields in Sustainable Agriculture: Application of Big Data Analytics and Artificial Intelligence - Divya Nimma; Jyoti A. Dhanke; G. S. N. Murthy; Sachin Dadu Khandekar; J. Hymavathi; Pradeep Jangir; Mahesh Singh (Remote Sensing in Earth Systems Sciences, 2025)

Effect of integrated disease management modules against major diseases (bacterial blight/root rot and downy mildew) of opium poppy - Shivam Singh; R. S. Mishra; S. K. Singh; M. K. Maurya; J. R. Yadav; Divya Singh; Abhishek Kumar; V. V. Raghuvanshi (Vegetos, 2025)

Population frequency distribution and introgression of Alternaria species causing leaf blight of sunflower, India - Divya shree; C.P. Manjula; M.K. Prasanna Kumar; K.B. Palanna; J. Harish; Pasumarthi Venkata Dinesh Kumar; Farooq khan (Physiological and Molecular Plant Pathology, 2025)

Allometric scaling and carbon sequestration in agroforestry species of the Western Himalayas: a model-based approach - Megha VR; R. Kaushal; Sadikul Islam; Uday Mandal; Harsh Mehta; Rajkumar; J. M. S. Tomar; Anand Kumar Gupta; Anupam Barh; Vishwal Madhav P; Vibha Singhal; Rajiv Pandey; et al. (Environmental Monitoring and Assessment, 2025)

An evaluation of in utero polycyclic aromatic hydrocarbon exposure on the neonatal meconium microbiome - Divya Keerthy; Miranda J. Spratlen; Lingsheng Wen; Dwayne Seeram; Heekuk Park; Lehyla Calero; Anne-Catrin Uhlemann; Julie B. Herbstman (Environmental Research, 2024)

Trends in pancreatic cancer mortality in the United States 1999–2020: a CDC database population-based study - Alexander J. Didier; Swamroop Nandwani; Alan M. Fahoury; Daniel J. Craig; Dean Watkins; Andrew Campbell; Caleb T. Spencer; Macelyn Batten; Divya Vijendra; Jeffrey M. Sutton (Cancer Causes & Control, 2024)
Introduction Pancreatic cancer is a significant public health concern and a leading cause of cancer-related deaths worldwide. This study aimed to investigate pancreatic cancer mortality trends and disparities in the United States (US) from 1999 to 2020. Methods Data were obtained from the Centers for Disease Control (CDC) Wide-Ranging Online Data for Epidemiologic Research database. Mortality rates were age-adjusted and standardized to the year 2000 US population. Joinpoint regression was used to analyze temporal trends in age-adjusted mortality rates (AAMRs) by sociodemographic and geographic variables. Results Between 1999 and 2020, pancreatic cancer led to a total of 810,628 deaths in the US, an average mortality of nearly 39,000 deaths per year. The AAMR slightly increased from 10.6 in 1999 to 11.1 in 2020, with an associated annual percent change (APC) of 0.2. Mortality rates were highest among individuals aged 65 and older. Black individuals experienced the highest overall pancreatic cancer-related AAMR at 13.8. Despite this, Black individuals experienced a decreasing mortality trend over time (APC −0.2) while White individuals experienced an increasing trend in mortality (APC 0.4). Additionally, individuals residing in rural areas experienced steeper rates of mortality increase than those living in urban areas (APC 0.6 for rural vs −0.2 for urban). White individuals in urban and rural populations experienced an increase in mortality, while Black individuals in urban environments experienced a decrease in mortality, and Black individuals in rural environments experienced stable mortality trends. Conclusions Mortality from pancreatic cancer continues to increase in the US, with racial and regional disparities identified in minorities and rural-dwelling individuals. These disparate findings highlight the importance of ongoing efforts to understand and address pancreatic cancer treatment and outcomes disparities in the US, and future studies should further investigate the underlying etiologies of these disparities and potential for novel therapies to reduce the mortality.

Geospatial assessment of agroforestry land use systems using very high-resolution satellite images and artificial intelligence - Shivam Trivedi; P. V. Vinod; B. Chandrasekaran; M. K. Nagashree; S. Rama Subramoniam; V. B. Manjula; Amrita Singh; J. K. Mani; Arun S. Suryavanshi; Sushilkumar B. Rehpade; Akash Goyal; N. R. Shankar Ram; et al. (Agroforestry Systems, 2024)

Modulating temperature for Cu2ZnSnS4 (CZTS) synthesis via hot injection method and studying the photocatalytic efficiencies for the degradation of rhodamine 6G and methylene blue pollutants - Valentina Nava Murillo; Darshana Rajput; J. Manríquez; Erika Bustos; Jose de Jesus Perez Bueno; Divya Singh; Harish Dubey; Carlos Eduardo Frontana Vazquez; S. Godavarthi; Zakaryaa Zarhri; Fabrizio Olivito; Ashutosh Sharma; et al. (Environmental Research, 2024)

Initial Mild Traumatic Brain Injury Characteristics and Recovery Patterns Among Females Across the United States Military Service Academies: A Report from the NCAA-DoD CARE Consortium - Landon B. Lempke; Elsa Ermer; Adrian J. Boltz; Jaclyn Caccese; Thomas A. Buckley; Kenneth L. Cameron; Sara P. D. Chrisman; Christopher D’Lauro; James T. Eckner; Carrie Esopenko; Tamerah N. Hunt; Divya Jain; et al. (Annals of Biomedical Engineering, 2024)

Morphological and molecular data establishes Clinostomum dolichorchum n. sp. (Digenea: Clinostomidae) in the great blue heron Ardea herodias L. and American bullfrog Rana catesbeiana Shaw - Jonah A. Nguyen; Ethan T. Woodyard; Chris T. McAllister; Susan V. Marcquenski; Divya Rose; Celene M. Slifka; Logan R. S. Robison; Matt J. Griffin; T. Graham Rosser (Systematic Parasitology, 2024)

Synthesis, Structural, and Optical Properties of 2-(2-methyl 8-hydroxyquinoline) Magnesium Nanorods for Optical Display Systems - J. P. Suchitra; J. Christina Rhoda; V. Bharathi Devi; P. Divya; Helen Merina Albert (Journal of Fluorescence, 2024)

Single cell RNA-seq: a novel tool to unravel virus-host interplay - Harsh Rajeshbhai Jogi; Nabaneeta Smaraki; Sonali Sonejita Nayak; Divya Rajawat; Dhaval J. Kamothi; Manjit Panigrahi (VirusDisease, 2024)

Low clouds over the subtropical Indian Ocean and sub-seasonal circulation associations with the Indian summer monsoon - T. Gokul; R. K. Vellore; D. C. Ayantika; V. Divya; R. Krishnan; M. J. K. Reji (Climate Dynamics, 2024)

Diversity of Indian rice cultivars and landraces for seedling vigour and their association for yield related traits - Sai Teja Dayala; Divya Balakrishnan; Sonali Kar; J. L. Ganguli; L. V. Subba Rao; R. M. Sundaram (Vegetos, 2024)

Identification and validation of blast resistance Pi1 gene in the derived mapping population of rice variety, NLR34449 through molecular markers - Dasari Aleena; V. Padma; G. Rekha; M. S. Prasad; M. S. Madhav; E. Punniakoti; T. Dilip; P. Sinha; M. Kousik; M. A. Das; M. Anila; Lal Ahmmed; et al. (Indian Phytopathology, 2023)

Metabolomics targets tissue-specific responses in alleviating the negative effects of salinity in tef (Eragrostis tef) during germination - Bahareh Sadat Haddadi; Rui Fang; Aiswarya Girija; Divya Kattupalli; Emma Widdowson; Manfred Beckmann; Rattan Yadav; Luis A. J. Mur (Planta, 2023)
Main conclusion Salinity induced metabolite responses resulted in differential accumulation of flavonoids and antioxidant metabolites in shoots and roots suggesting improved antioxidant capacity in providing salt-adaptive phenotype of tef seedling. Abstract Tef [( Eragrostis tef ) (Zucc.) Trotter] is an important ‘cash crop’ of Ethiopia grown mainly for human food, and development of elite tef cultivars with better performance is vital to Ethiopian farmers and breeders. Soil salinity is one of the key constraints that affects tef yield in the Ethiopian lowlands and Rift valley where cultivation of tef is limited. Being a minor crop, the responses of tef towards salinity is unknown. Salinity involves physiological and metabolite reprogramming that can have major impact on germination and seedling establishment. Here we evaluate the in vitro effect of NaCl on tef germination and associate this with metabolomic approaches to suggest salt tolerance mechanisms. In this study, 19 tef varieties were screened for NaCl tolerance and were investigated using untargeted metabolomics. Screened tef varieties showed differential germination rates with NaCl treatment varying from < 20 to 100%. Viable seedlings exposed to NaCl exhibited purple-red pigment accumulation in the roots except for Beten and Tullu nasy varieties. Metabolite comparisons between shoots and roots showed significant differences and, in particular, roots of salt tolerant tef varieties accumulated flavonoid derivatives as well as sugars and cell wall associated metabolites. These metabolic changes were correlated with patterns of antioxidant capacities and total flavonoid content in shoots and roots and suggested a mitigating response by tef to salinity. Our study highlights the role of flavonoid accumulation following salt stress on tef seedlings and further these findings could be used as targets for selective tef breeding.

Linking the role of melatonin in plant stress acclimatization - Ashutosh Singh; Himanshu Pandey; Apurba Pal; Divya Chauhan; Saurabh Pandey; Dinkar J Gaikwad; Chandrasekhar Sahu; Kousik Atta (South African Journal of Botany, 2023)

Global assessment of the biodiversity safeguards of development banks that finance infrastructure - Divya Narain; Laura J. Sonter; Alex Mark Lechner; James E. M. Watson; Jeremy S. Simmonds; Martine Maron (Conservation Biology, 2023)
Infrastructure development is a major driver of biodiversity loss globally. With upward of US$2.5 trillion in annual investments in infrastructure, the financial sector indirectly drives this biodiversity loss. At the same time, biodiversity safeguards (project‐level biodiversity impact mitigation requirements) of infrastructure financiers can help limit this damage. The coverage and harmonization of biodiversity safeguards are important factors in their effectiveness and therefore warrant scrutiny. It is equally important to examine the extent to which these safeguards align with best‐practice principles for biodiversity impact mitigation outlined in international policies, such as that of the International Union for Conservation of Nature. We assessed the biodiversity safeguards of public development banks and development finance institutions for coverage, harmonization, and alignment with best practice. We used Institute of New Structural Economics and Agence Française de Développement's global database to identify development banks that invest in high‐biodiversity‐footprint infrastructure and have over US$500 million in assets. Of the 155 banks, 42% ( n = 65) had biodiversity safeguards. Of the existing safeguards, 86% (56 of 65) were harmonized with International Finance Corporation (IFC) Performance Standard 6 (PS6). The IFC PS6 (and by extension the 56 safeguard policies harmonized with it) had high alignment with international best practice in biodiversity impact mitigation, whereas the remaining 8 exhibited partial alignment, incorporating few principles that clarify the conditions for effective biodiversity offsetting. Given their dual role in setting benchmarks and leveraging private finance, infrastructure financiers in development finance need to adopt best‐practice biodiversity safeguards if the tide of global biodiversity loss is to be stemmed. The IFC PS6, if strengthened, can act as a useful template for other financier safeguards. The high degree of harmonization among safeguards is promising, pointing to a potential for diffusion of practices.

A comprehensive health effects assessment of the use of sanitizers and disinfectants during COVID-19 pandemic: a global survey - Fallah Hashemi; Lori Hoepner; Farahnaz Soleimani Hamidinejad; Daniela Haluza; Sima Afrashteh; Alireza Abbasi; Elma Omeragić; Belma Imamović; Narin A. Rasheed; Taqi M. J. Taher; Fitri Kurniasari; Dhuha Youssef Wazqar; et al. (Environmental Science and Pollution Research, 2023)

Bioengineering of biowaste to recover bioproducts and bioenergy: A circular economy approach towards sustainable zero-waste environment - Vinay Kumar; Alisa S. Vangnai; Neha Sharma; Komalpreet Kaur; Pritha Chakraborty; Mridul Umesh; Barkha Singhal; Divya Utreja; Edgar Uquiche Carrasco; Rodrigo Andler; Mukesh Kumar Awasthi; Mohammad J. Taherzadeh (Chemosphere, 2023)

Expanding phenotype of ATP1A3 mutation - Ajith Cherian; J. Nandana; K. P. Divya; Sharath Chandra Shetty (Acta Neurologica Belgica, 2022)

E-waste recycling practices: a review on environmental concerns, remediation and technological developments with a focus on printed circuit boards - Saurabh P. Tembhare; Bharat A. Bhanvase; Divya P. Barai; Sanjay J. Dhoble (Environment, Development and Sustainability, 2022)

A decision support tool for integrated fisheries bycatch management - Eric Gilman; Martin Hall; Hollie Booth; Trisha Gupta; Milani Chaloupka; Hannah Fennell; Michel J. Kaiser; Divya Karnad; E. J. Milner-Gulland (Reviews in Fish Biology and Fisheries, 2022)
Participatory decision tools enable stakeholders to reconcile conflicting natural resources management objectives. Fisheries targeting highly productive species can have profound impacts on co-occurring bycatch species with low fecundity and other life history traits that make them vulnerable to anthropogenic sources of mortality. This study developed a decision tool for integrated bycatch management for data-limited to data-rich fisheries, improving upon current piecemeal approaches. First, through a systematic literature review, participants compile a comprehensive database of methods to mitigate the catch and fishing mortality of threatened bycatch species. These mitigation methods are then categorized into tiers of a sequential mitigation hierarchy, where interventions that avoid capture are considered before those that minimize catchability, followed by methods that minimize fishing mortality, before approaches that offset residual impacts. The methods are also assembled within an evidence hierarchy, where findings from meta-analytic modelling studies are more robust and generalizable than from individual studies. The decision tool enables stakeholders to evaluate alternative bycatch management strategies’ efficacy at meeting specific and measurable objectives for mitigating the catch and mortality of bycatch and for costs from multispecies conflicts, economic viability, practicality and safety, while accounting for the fishery-specific feasibility of compliance monitoring of alternative bycatch management measures. Ongoing adaptation of the bycatch management framework addresses findings from performance assessments, updated evidence, new mitigation methods and changes to governance systems. The proposed decision tool therefore enables stakeholders to develop bycatch management frameworks that provide precautionary protection for the most vulnerable populations with acceptable tradeoffs.

Correction to: Quantitative proteomic analysis reveals differential modulation of crucial stage specific proteins during promastigote to amastigote differentiation in Leishmania donovani - Chinmayee Bar Routaray; Vaibhavee Choudhari; Divya Prakash; Rajendra Patil; Surabhi Jagtap; Shakuntala Bai; Mahesh J. Kulkarni; Suresh V. Kuchipudi; Kalpana Pai (Journal of Proteins and Proteomics, 2022)

Quantitative proteomic analysis reveals differential modulation of crucial stage specific proteins during promastigote to amastigote differentiation in Leishmania donovani - Chinmayee Bar Routaray; Vaibhavee Choudhari; Divya Prakash; Rajendra Patil; Surabhi Jagtap; Shakuntala Bai; Mahesh J. Kulkarni; Suresh V. Kuchipudi; Kalpana Pai (Journal of Proteins and Proteomics, 2022)

Impact of polystyrene microplastics on major marine primary (phytoplankton) and secondary producers (copepod) - P. Raju; P. Santhanam; S. Sonai Pandian; M. Divya; A. Arunkrishnan; K. Nanthini Devi; S. Ananth; J. Roopavathy; P. Perumal (Archives of Microbiology, 2022)

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Optical Clearing of Skeletal Muscle Bundles Engineered in 3-D Printed Templates - Nethika R. Ariyasinghe; Jeffrey W. Santoso; Divya Gupta; Mark J. Pincus; Paul R. August; Megan L. McCain (Annals of Biomedical Engineering, 2021)

Specific H+ level is crucial for accurate phosphate quantification using ascorbate as a reductant - Subramaniyan Divya; Peddisetty Sharmila; J. Dinakaran; Gupta Yamal; Kottapalli S. Rao; P. Pardha-Saradhi (Protoplasma, 2020)

Genetic population structure of a highly migratory Hilsa Shad, Tenualosa ilisha, in three river systems, inferred from four mitochondrial genes analysis - Vindhya Mohindra; B. K. Divya; Rajesh Kumar; Rajeev K. Singh; Arvind Kumar Dwivedi; Sangeeta Mandal; Prachi Masih; Kuldeep K. Lal; J. K. Jena (Environmental Biology of Fishes, 2019)

Macromolecular properties and partial amino acid sequence of a Kunitz-type protease inhibitor from okra (Abelmoschus esculentus) seeds - Debparna Datta; Gottfried Pohlentz; Saradamoni Mondal; M Bala Divya; Lalitha Guruprasad; Michael Mormann; Musti J Swamy (Journal of Biosciences, 2019)

Genomic characterisation of Cuiaba and Charleville viruses: arboviruses (family Rhabdoviridae, genus Sripuvirus) infecting reptiles and amphibians - Nikos Vasilakis; Robert B. Tesh; Steven G. Widen; Divya Mirchandani; Peter J. Walker (Virus Genes, 2019)

Muscle transcriptome resource for growth, lipid metabolism and immune system in Hilsa shad, Tenualosa ilisha - B. K. Divya; Vindhya Mohindra; Rajeev K. Singh; Prabhaker Yadav; Prachi Masih; J. K. Jena (Genes & Genomics, 2019)

Map-based cloning and validation of a gall midge resistance gene, Gm8, encoding a proline-rich protein in the rice variety Aganni - D. Divya; Nihar Sahu; Suresh Nair; J. S. Bentur (Molecular Biology Reports, 2018)

Development and Characterization of SSR Markers to Study Genetic Diversity and Population Structure of Horsegram Germplasm (Macrotyloma uniflorum) - R. K. Chahota; Divya Shikha; Maneet Rana; Vikas Sharma; Akshay Nag; T. R. Sharma; J. C. Rana; Hideki Hirakawa; Sachiko Isobe (Plant Molecular Biology Reporter, 2017)

The Neuropeptide Orexin-A Inhibits the GABAA Receptor by PKC and Ca2+/CaMKII-Dependent Phosphorylation of Its β1 Subunit - Divya Sachidanandan; Haritha P. Reddy; Anitha Mani; Geoffrey J. Hyde; Amal Kanti Bera (Journal of Molecular Neuroscience, 2017)

Optimisation of Hidden Markov Model using Baum–Welch algorithm for prediction of maximum and minimum temperature over Indian Himalaya - J C JOSHI; TANKESHWAR KUMAR; SUNITA SRIVASTAVA; DIVYA SACHDEVA (Journal of Earth System Science, 2017)

Modulation of digestive enzymes, GH, IGF-1 and IGF-2 genes in the teleost, Tilapia (Oreochromis mossambicus) by dietary curcumin - Sebastian J. Midhun; Damodaran Arun; Lincy Edatt; M. V. Sruthi; V. V. Thushara; Oommen V. Oommen; V. B. Sameer Kumar; Lekha Divya (Aquaculture International, 2016)

Divergent Perspectives on Landscape Connectivity Reveal Consistent Effects from Genes to Communities - Robert J. Fletcher; Noah S. Burrell; Brian E. Reichert; Divya Vasudev; James D. Austin (Current Landscape Ecology Reports, 2016)

Analysis of SSH library of rice variety Aganni reveals candidate gall midge resistance genes - Dhanasekar Divya; Y. Tunginba Singh; Suresh Nair; J. S. Bentur (Functional & Integrative Genomics, 2016)

Characterization of microsatellite markers in silver pomfret, Pampus argenteus (Perciformes: Stromateidae) through cross-species amplification and population genetic applications - C. MOHITHA; LINU JOY; P. R. DIVYA; A. GOPALAKRISHNAN; V. S. BASHEER; MOHAMMED KOYA; J. K. JENA (Journal of Genetics, 2015)

Molecular phylogenetics of three species of the genus Rastrelliger using mitochondrial DNA markers - V. S. Basheer; C. Mohitha; N. Vineesh; P. R. Divya; A. Gopalakrishnan; J. K. Jena (Molecular Biology Reports, 2015)

Overexpression of EaDREB2 and pyramiding of EaDREB2 with the pea DNA helicase gene (PDH45) enhance drought and salinity tolerance in sugarcane (Saccharum spp. hybrid) - Sruthy Maria Augustine; J. Ashwin Narayan; Divya P. Syamaladevi; C. Appunu; M. Chakravarthi; V. Ravichandran; Narendra Tuteja; N. Subramonian (Plant Cell Reports, 2015)

Ultraviolet and 5′Fluorodeoxyuridine Induced Random Mutagenesis in Chlorella vulgaris and Its Impact on Fatty Acid Profile: A New Insight on Lipid-Metabolizing Genes and Structural Characterization of Related Proteins - Josephine Anthony; Vijaya Raghavan Rangamaran; Dharani Gopal; Kumar T. Shivasankarasubbiah; Mary Leema J. Thilagam; Magesh Peter Dhassiah; Divya Shridhar M. Padinjattayil; VinithKumar N. Valsalan; Vijayakumaran Manambrakat; Sivakumar Dakshinamurthy; Sivaraman Thirunavukkarasu; Kirubagaran Ramalingam (Marine Biotechnology, 2015)

Mitochondrial ATPase 6/8 genes reveal genetic divergence in the Coilia dussumieri (Valenciennes, 1848) populations of north east and northwest coasts of India - A. Kathirvelpandian; A. Gopalakrishnan; W. S. Lakra; Gopal Krishna; Rupam Sharma; P. R. Divya; Raj Kumar; J. K. Jena (Molecular Biology Reports, 2014)

Urgency for sustainable development in coastal urban areas with reference to weather pattern, land use, and water quality - A. M. Sheela; J. Letha; K. Swarnalatha; K. V. Baiju; Divya Sankar (Environmental Monitoring and Assessment, 2014)

Comparative study of toxic chlorophenolic compounds generated in various bleaching sequences of wheat straw pulp - Rachna Malhotra; Divya Prakash; Sudheer Kumar Shukla; Taesung Kim; Satish Kumar; N. J. Rao (Clean Technologies and Environmental Policy, 2013)

Devising the Optimal Preclinical Oncology Curriculum for Undergraduate Medical Students in the United States - Nicholas J. DeNunzio; Lija Joseph; Roxane Handal; Ankit Agarwal; Divya Ahuja; Ariel E. Hirsch (Journal of Cancer Education, 2013)

Bayesian Decision‐Network Modeling of Multiple Stakeholders for Reef Ecosystem Restoration in the Coral Triangle - DIVYA A. VARKEY; TONY J. PITCHER; MURDOCH K. McALLISTER; RASHID S. SUMAILA (Conservation Biology, 2013)
Proposals for marine conservation measures have proliferated in the last 2 decades due to increased reports of fishery declines and interest in conservation. Fishers and fisheries managers have often disagreed strongly when discussing controls on fisheries. In such situations, ecosystem‐based models and fisheries‐stock assessment models can help resolve disagreements by highlighting the trade‐offs that would be made under alternative management scenarios. We extended the analytical framework for modeling such trade‐offs by including additional stakeholders whose livelihoods and the value they place on conservation depend on the condition of the marine ecosystem. To do so, we used Bayesian decision‐network models (BDNs) in a case study of an Indonesian coral reef fishery. Our model included interests of the fishers and fishery managers; individuals in the tourism industry; conservation interests of the state, nongovernmental organizations, and the local public; and uncertainties in ecosystem status, projections of fisheries revenues, tourism growth, and levels of interest in conservation. We calculated the total utility (i.e., value) of a range of restoration scenarios. Restricting net fisheries and live‐fish fisheries appeared to be the best compromise solutions under several combinations of settings of modeled variables. Results of our case study highlight the implications of alternate formulations for coral reef stakeholder utility functions and discount rates for the calculation of the net benefits of alternative fisheries management options. This case study may also serve as a useful example for other decision analyses with multiple stakeholders. Modelo de Red de Decisión Bayesiana de Múltiples Actores Interesados en la Restauración de Ecosistemas de Arrecife en el Triángulo de Coral

Design of peptide affinity ligands for S-protein: a comparison of combinatorial and de novo design strategies - Divya Chandra; Christopher J. Morrison; James Woo; Steven Cramer; Pankaj Karande (Molecular Diversity, 2013)

Fe3O4-PEI-RITC Magnetic Nanoparticles with Imaging and Gene Transfer Capability: Development of a Tool for Neural Cell Transplantation Therapies - Humphrey H. P. Yiu; Mark R. Pickard; Cristina I. Olariu; Stephen R. Williams; Divya M. Chari; Matthew J. Rosseinsky (Pharmaceutical Research, 2012)

Effect of triadimefon: a triazole fungicide on oxidative stress defense system and eugenol content in Ocimum tenuiflorum L. - V. Divya Nair; R. Gopi; M. Mohankumar; J. Kavina; R. Panneerselvam (Acta Physiologiae Plantarum, 2012)

Eye–hand coordination of symmetric bimanual reaching tasks: temporal aspects - Divya Srinivasan; Bernard J. Martin (Experimental Brain Research, 2010)

IL-33 synergizes with IgE-dependent and IgE-independent agents to promote mast cell and basophil activation - Matthew R. Silver; Alexander Margulis; Nancy Wood; Samuel J. Goldman; Marion Kasaian; Divya Chaudhary (Inflammation Research, 2010)

Transcriptome profiling identified novel genes associated with aluminum toxicity, resistance and tolerance in Medicago truncatula - Divya Chandran; Natasha Sharopova; Sergey Ivashuta; J. Stephen Gantt; Kathryn A. VandenBosch; Deborah A. Samac (Planta, 2008)

Archaeal histone stability, DNA binding, and transcription inhibition above 90°C - Divya Soares; Isabel Dahlke; Wen-Tyng Li; Kathleen Sandman; Carina Hethke; Michael Thomm; J. N. Reeve (Extremophiles, 1998)